A Systems Thinking Framework for Knowledge Management - SHARMA, DR. DINESH (The journal of contemporary issues in business and government, 2021)
To handle information Myriad frameworks have been created. Nevertheless, the field was slow in formulating a widely accepted, systematic knowledge management system. This paper reviews the existing framework for knowledge management and gives suggestions as to what a general framework should include. The distinctive characteristic of this work is that it emphasizes putting information management in a broader sense of system thought in order to better identify and appreciate the driving influences on its success or failure.Managing knowledge is a young discipline for unestablished, commonly known, codified structure. Despite this, knowledge management approaches have implemented in a wide range of organizations. on the other hand, such methods do not sufficiently meet the needs of organizational Knowledge Management. This written product will have more lasting strength as a discipline if theories and concepts unifying across the discipline are aligned with the information management methods, methodologies, tools and techniques. Knowledge management is an evolving field that command concentration and hold up from the engineering community. A lot of companies are now engaging in knowledge technology to leverage resources to its stakeholders and clients both within and outside their companies. Managing understanding involves an organization's meaning creation of the intangible assets.